Avaliação dos aspectos da dieta alimentar de Pimelodus maculatus em dois importantes tributários do reservatório de Jurumirim, Alto Rio Paranapanema-SP - Silva, Graciette Perissinotto da [UNESP] (2013)
The species Pimelodus maculatus is one of the most abundant fish in many artificial reservoirs. Shows feeding plasticity and exploits all trophic levels in aquatic ecosystems. This study aimed to analyze and compare aspects of the diet of P. maculatus in two important tributaries (Taquari and Veados rivers) in the upper Paranapanema River system, and also investigate possible differences in the condition factor using its feeding habit as reference. Samplings were carried out every three months during 2011 and 2012 in two tributaries of Jurumirim's dam. After biometric analysis, fish were dissected to remove the stomachs that were fixed in formaldehyde 10% and conserved in alcohol 70%. The stomach content was analyzed under stereomicroscope and the food items were identified until the least possible taxonomic level. The diet was characterized based on the Alimentary Index (IAi). Feeding strategy and aspects of species autoecology were evaluated by the relation between abundance of prey-specific (Pi) and occurrence frequency (Fo) of the prey, and also was calculated the niche width of Levin (B). The condition factor was also established and values obtained in samples of both rivers were compared, correlating them with diet of the species